Ice‐melt rates during volcanic eruptions within water‐drained, low‐pressure subglacial cavities. Issue 2 (18th February 2016) - Woodcock, D. C.; Lane, S. J.; Gilbert, J. S.
Abstract: Subglacial volcanism generates proximal and distal hazards including large‐scale flooding and increased levels of explosivity. Direct observation of subglacial volcanic processes is infeasible; therefore, we model heat transfer mechanisms during subglacial eruptions under conditions where cavities have become depressurized by connection to the atmosphere. We consider basaltic eruptions in a water‐drained, low‐pressure subglacial cavity, including the case when an eruption jet develops. Such drained cavities may develop on sloping terrain, where ice may be relatively shallow and where gravity drainage of meltwater will be promoted. We quantify, for the first time, the heat fluxes to the ice cavity surface that result from steam condensation during free convection at atmospheric pressure and from direct and indirect radiative heat transfer from an eruption jet. Our calculations indicate that the direct radiative heat flux from a lava fountain (a "dry" end‐member eruption jet) to ice is c. 25 kW m −2 and is a minor component. The dominant heat transfer mechanism involves free convection of steam within the cavity; we estimate the resulting condensation heat flux to be c. 250 kW m −2 . Absorption of radiation from a lava fountain by steam enhances convection, but the increase in condensing heat flux is modest at c. 25 kW m −2 . Overall, heat fluxes to the ice cavity surface are likely to be no greater than c. 300 kW m −2 . These are comparable with heat fluxes obtained by single phase convection of water in a subglacial cavity but much less than those obtained by two‐phase convection. Key Points: Heat fluxes in drained, low‐pressure subglacial eruption cavities are estimated Heat fluxes are lower than those inferred from recent volcanic eruptions